Hygiene and sanitation practices on street food vendors in Malaysia - Nur Idayu Izhab; Nur Hidayah Dahrial; Nurul Fatihah Badurdin; Yeo Li Ying (2021)
This study focuses on street food vendors in the food and beverage industry. The study examines hygiene and sanitation practices on street food vendors in Malaysia. Thus, this study investigates the relationship between food knowledge, attitude, food safety practice towards food safety implementation among street food vendors in Malaysia. KAP Model also be used in this research. Quantitative research was carried out to accomplish this research. Convenience sampling was used and responses from 375 respondents were collected. Descriptive analysis, reliability test, and Pearson Correlation were used to analyse the data. The final result showed a significant relationship between food knowledge, attitude, and food safety practice with the food safety implementation. Preparation practice and environmental hygiene are found as additional variables that can be used in future research.